Performance analysis and optimization of a space-time selective PIC for CDMA systems. - Fantacci, R.
This paper deals with an efficient receiver for applications in direct sequence-code-division multiple access wireless communication systems. This receiver combines a modified scheme of a parallel interference cancellation detector with antenna arrays with optimum beamforming and is used at the base station for the detection of asynchronous user signals. Each user's transmission channel is assumed to be a multipath frequency-selective independent Rayleigh fading channel. The receiver operates by dividing the signals into reliable and unreliable sets following space-time combining. The reliable signals are detected and canceled from the whole signal received at each sensor. Unreliable signals are then detected to improve the decision reliability. The receiver performance in terms of bit-error probability is analytically derived and optimized. According to the analytical and simulation results, this receiver outperforms previously proposed schemes and, thanks to its low implementation complexity, real-time operation is achieved.
Keywords: DS-CDMA system; Rayleigh fading channel; Adaptive antenna arrays; Asynchronous user signal detection; Bit error probability; Direct sequence-code division multiple access technique; Multipath frequency-selective channel; Multiple access interference cancellation; Optimum beamforming; Parallel interference cancellation detector; Space-time combining; Space-time selective PIC; Wireless communication system